The politics of decline understanding post-war Britain - Tomlinson, Jim (Longman, 2001)
The key aim of the book is to show how economic decline has always been a highly politicised concept, forming a central part of post-war political argument. In doing so, Tomlinson reveals how the term has been used in an exceptionally tendentious manner to advance particular political causes.